2022
DOI: 10.1002/ijgo.14562
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal respiratory allergy on obstetrics and perinatal outcomes: A nested case–control study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…This may be due to reduce statistical power for these secondary outcomes. Furthermore, in another study recently published by our group with a higher number of cases, we found significant associations 29 . The rates of PTD and LBW in the present study were similar to other published data, which established the prevalence of both perinatal outcomes to range from 5% to 13% and from 8% to 16%, respectively 3,6,12–14,18 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may be due to reduce statistical power for these secondary outcomes. Furthermore, in another study recently published by our group with a higher number of cases, we found significant associations 29 . The rates of PTD and LBW in the present study were similar to other published data, which established the prevalence of both perinatal outcomes to range from 5% to 13% and from 8% to 16%, respectively 3,6,12–14,18 .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, in another study recently published by our group with a higher number of cases, we found significant associations. 29 The rates of PTD and LBW in the present study were similar to other published data, which established the prevalence of both perinatal outcomes to range from 5% to 13% and from 8% to 16%, respectively. 3 , 6 , 12 , 13 , 14 , 18 However, due to the sample size in the allergic group, no meaningful conclusions could be drawn regarding PTD and LBW.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation